Translation Of Humour In Subtitles Of Personification-Based Animation From English Into Persian - Ghassemiazghandi, Mozhgan (2019)
Audiovisual translation, especially subtitling, attracts the attention of many scholars. However, the translation of Persian subtitles is scarce. The present study attempts to investigate the translation of humour in subtitles into Persian and determine the extent direct translation strategies are utilized. The study focuses on personification-based animation subtitles and primarily on three types of humour -universal, cultural and linguistic- from Schmitz's (2002) categorization of humour. The definition of transferring strategies here is adopted from Gottlieb (1992). The analysis is conducted in the light of the Sapir-Whorf hypothesis as the underlying theoretical framework of the study. Sixteen animation form the corpus of the study. The result indicates that direct translation strategies are prevalent strategies. Such usage suggests that the translation is aided by the simplicity of the source language and the non-verbal elements of the animation.